Diagnostic accuracy of confocal laser endomicroscopy for the characterization of liver nodules. Issue 1 (January 2017) - Pierangelo, Angelo; Fuks, David; Validire, Pierre; Benali, Ali; Gayet, Brice
Abstract : Objectives: Probe-based confocal laser endomicroscopy (pCLE) is a promising new imaging technique enabling in-vivo analysis of tissues at the cellular level, in real time. The aim of the present study was to prospectively evaluate the feasibility and accuracy of indocyanine green-aided pCLE for the diagnosis of malignant liver nodules. Patients and methods: From October 2014 to July 2015, liver specimens from 30 consecutive patients were analyzed ex vivo using pCLE directly after resection, with indocyanine green as contrast agent. The final diagnosis was obtained histologically, as per standard of care. In phase 1, a pathologist and a physicist established pCLE image criteria to distinguish normal parenchyma, malignant nodules, and metastases that had completely responded to chemotherapy. In phase 2, a pathologist and a surgeon reviewed selected videos retrospectively to assess the effectiveness of these. Results: In phase 1, the healthy nodules were characterized by fluorescent hepatocytes with nonfluorescent nuclei and the malignant nodules were identified as strongly fluorescent, irregular cancer-cell clusters. The extracellular matrix was substantially less fluorescent compared with the cancerous clusters of cells. After chemotherapy, a very dense and strongly fluorescent fibrosis replaced tubular structures of cancerous cells. The retrospective evaluation in phase 2 resulted in 78 and 100% sensitivity, 100 and 89% specificity, 90 and 100% positive predictive value, and 90 and 100% negative predictive value for the surgeon and the pathologist, respectively, for the detection of malignant nodules. Conclusion: This series emphasized that characterization of liver metastases is possible with pCLE, with high performance results. Abstract : Supplemental Digital Content is available in the text.